2021
DOI: 10.1021/acsapm.1c00152
|View full text |Cite
|
Sign up to set email alerts
|

Phenoxazine-Containing Polyaniline Derivatives with Improved Electrochemical Stability and Processability

Abstract: Polyaniline (PANI) is one of the most accessible conducting polymers and is known for its environmental stability in its partially oxidized conductive state. However, it is difficult to process and undergoes electrochemical degradation between its partially and fully oxidized states. While there have been several approaches to address PANI’s processability, little has been done to address its electrochemical instability. We have prepared two polyaniline derivatives that contain a phenoxazine unit copolymerized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 70 publications
(111 reference statements)
1
19
0
Order By: Relevance
“…We recently reported the synthesis of a phenoxazine PANI derivative that showed excellent electrochemical stability . However, phenoxazine is expensive, and its preparation requires a multistep approach.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We recently reported the synthesis of a phenoxazine PANI derivative that showed excellent electrochemical stability . However, phenoxazine is expensive, and its preparation requires a multistep approach.…”
Section: Resultsmentioning
confidence: 99%
“…As such, the electrical conductivity of the polymers was determined using a four-point probe apparatus. Films of Cbz-PANI-1 and Cbz-PANI-2 were prepared by drop-casting a 5 mg/mL EtOH solution of the polymers onto the substrate, which were then subjected to slow drying over m -cresol vapor at 100 °C for 24 h. In our previous studies, it was shown that m -cresol increased the conductivity by changing the morphology of the polymers from aggregated particles to thick sheet-like structures . The conductivity was determined to be 2.82 S cm –1 for Cbz-PANI-1 and 0.70 S cm –1 for Cbz-PANI-2 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The P1 and P2 polymers were synthesized according to a previous work. [162,163] 1 H NMR spectra were recorded on a Bruker spectrometer (500 MHz) in deuterated solvent at room temperature. The chemical shifts were expressed in parts per million (ppm) downfield from SiMe 4 after the NMR data were processed by Mestre Nova.…”
Section: Methodsmentioning
confidence: 99%
“…Almtiri et al [ 125 ] have prepared two PANI derivatives that contain a phenoxazine unit copolymerized with 2,5-dimethyl-p-phenylenediamine and p-phenylenediamine and determined their electrochromic properties. PANI nanofilaments were obtained by electropolymerization of aniline through the vertically aligned silica nanochannels [ 126 ] .…”
Section: Spectroelectrochemical Approach To Study Electroactive Compo...mentioning
confidence: 99%